THE THEORETICAL MODEL OF THE PEDAGOGICAL SYSTEM OF FORMATION OF THE ABILITIES OF FOREIGN-LANGUAGE BUSINESS COMMUNICATION SKILLS AMONG STUDENTS OF THE BACHELOR DEGREE IN THE POWER INDUSTRY AND ELECTRICAL EQUIPMENT - Yulia V. Shustova; Valentin N. Mikhelkevich (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article is focused on the theoretical model of the pedagogical system of formation of the abilities of foreign-language business communication skills among students of the bachelor degree in the Power Industry and Electrical Equipment. The functional and procedural characteristics of each of nine links of model of the system are considered. Special attention is paid to the description of information and didactic base and the intensive pedagogical technologies of formation of the abilities of foreign-language business communication. As part of information and didactic base, in addition to the traditional basic textbooks and manuals in a foreign language, electrotechnical dictionaries, catalogues and prospectuses in a foreign language, Internet resources, the author's manual "Intensive English for Electricians" is also presented. The used intensive pedagogical technologies are classified by the form of the organization of the educational process, by the way of submission of educational information; the training in a group is got out selectively depending on the type of an educational activity in class in a foreign language (reading, writing, audition, speaking) and stages (a course, a semester) of training the students.